Ad hoc method for the assessment of animal diseases caused by bacteria resistant to antimicrobials. (3rd June 2021) - ,; Nielsen, Søren Saxmose; Bicout, Dominique Joseph; Calistri, Paolo; Canali, Elisabetta; Drewe, Julian Ashley; Garin‐Bastuji, Bruno; Gonzales Rojas, Jose Luis; Gortazar Schmidt, Christian; Herskin, Mette; Michel, Virginie; Miranda Chueca, Miguel Angel; et al.
Abstract: The European Commission requested EFSA assess antimicrobial‐resistant bacteria responsible for animal transmissible diseases, with a view to listing such pathogens for European Union action. This Scientific Opinion addresses the ad hoc method developed: (i) to give a global state of play as regards resistant animal pathogens that cause transmissible animal diseases, (ii) to identify the most relevant bacteria in the EU and (iii) to summarise their actual or potential animal health impact, and to perform their assessment for being listed and categorised according to the criteria of Articles 7, 5, 9 and 8 within the Animal Health Law (AHL) framework. An extensive literature review is carried out to give the global state of play of selected resistant bacteria that constitute a threat to animal health (i). An expert judgement procedure, based on the outcome of the literature review, is applied to identify which among those bacteria subjected to the literature review are the 'most relevant' in the European Union (ii). Their animal health impact in the European Union and their assessment for being listed and categorised according to the AHL framework will follow the 'ad hoc method for the assessment on listing and categorisation of animal diseases within the framework of the Animal Health Law' that EFSA has developed in the past (iii). The assessment of (i) and (ii) is addressed in distinct scientific opinions that are published separately by animal species of interest (dogs and cats, horses, pigs, poultry, cattle, small ruminants, rabbits and aquatic animal species). The assessment of (iii) is addressed in distinct scientific opinions and published separately by the animal pathogen.